Efektivitas Strategi Game Based Learning Untuk Meningkatkan Antusiasme Dan Keaktifan Siswa Dalam Layanan Bimbingan Klasikal - Wahyu Dwi Ningtyas; Vivi Rahmawati; Nining Solekah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The low enthusiasm and engagement of students must be improved to achieve the objectives of classical guidance. Positive indicators of enthusiasm and engagement include the willingness to ask questions, express opinions, show excitement during class interactions, and complete tasks effectively. This research aimed to enhance students' enthusiasm and engagement through a game-based learning strategy. The study utilized an experimental type of counseling action research, involving 32 students from class IX-C. Data collection techniques included observation, self-evaluation questionnaires, and documentation. The data were analyzed descriptively and comparatively. Results indicated a 20,84% increase in student enthusiasm and engagement, rising from an initial 63,54%. This improvement reflects the cumulative outcomes from pre-cycle to cycles I and II. Thus, it can be concluded that the game-based learning strategy effectively enhances students' enthusiasm and engagement in classical guidance.